UJI AKTIVITAS ANTIJAMUR EKSTRAK DAUN (Ipomoea carnea Jacq) TERHADAP Candida albicans - Lia Fikayuniar; Ermi Abriyani; Rizmayanti Intan Ferdiansah; Sumiyati Sumiyati; Santa Regina Sianipar; Selvia Aziza (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Infectious diseases can be transmitted from one person to another or from animals to humans of the causes of infection diseases is fungi. Fungi are microorganisms in the form of cells or branched threads. These microorganisms have a rigid cell wall and composed of polysaccharides or chitin, have nuclei and spores, are not chlorophyllous and do not multiply sexually and asexually. Based on this, research was carried using of the welling method on antifungal bioactivity as well as a thin layer chromatography test of spotting to determine the content of secondary metabolites contained in the leaves of kale fence. This study aims to determine the bioactivity of secondary metabolites in n-hexane extract, ethyl acetate, and methanol of kangkong pagar leaves (Ipomoea carnea Jacq) against Candida albicans fungi. This study made four different concentrations namely 60%, 80%, 100%, 120%, for positive control using ketoconazole and negative control using CMC 1%. Data analysis is using the One Way ANOVA test. From this study, the results were that kale fence leaf extract contains secondary metabolites, namely flavonoids, tannins, steroids. Then the results of the antifungal activity test of fencing kale leaves have activities that can inhibit fungi at a concentration of 120% with an inhibitory zone diameter of 11,254 mm so that they can be classified as strong antifungal bioactivity, in the results of the One Way ANOVA analysis of the three samples (N Hexana, Methanol and ethyl Acetate), it is known that the Sig value is 0.000 < 0.05 so it can be said that the rata_rata is